1982
DOI: 10.1007/bf00436093
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric ethanol antagonism in mice: Studies on oxygen, nitrogen, strain and sex

Abstract: Male and female C57BL/6J and male BALBc/J mice were injected with 3.6 g/kg ethanol or saline and exposed to 1-10 atmospheres absolute (ATA) air, to 1 ATA 80% helium-20% oxygen, or to 12 ATA helium-oxygen having oxygen partial pressures between 0.5 and 18 times normal. Hyperbaric helium-oxygen significantly reduced sleep-time and increased wake-up brain ethanol concentrations in all mice tested. The degree of antagonism was not enhanced by increasing the oxygen partial pressure. Hyperbaric air increased sleep-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This provides normal oxygenation and avoids complications from higher oxygen partial pressures. In addition, we replace the nitrogen in our gas mixture with helium to avoid the depressant effect of nitrogen at increased atmospheric pressure (Alkana and Malcolm 1982a).…”
Section: Atmospheric Conditionsmentioning
confidence: 99%
“…This provides normal oxygenation and avoids complications from higher oxygen partial pressures. In addition, we replace the nitrogen in our gas mixture with helium to avoid the depressant effect of nitrogen at increased atmospheric pressure (Alkana and Malcolm 1982a).…”
Section: Atmospheric Conditionsmentioning
confidence: 99%
“…In previous studies we observed that exposure to 12 atmospheres absolute (ATA) of a mixture of helium and oxygen antagonizes the acute depressant effect of ethanol in mice (5,(9)(10)(11)(12). The antagonismn does not reflect changes in the absorption, distribution, or elimination of ethanol; increases in the partial pressure of oxygen or helium; or alterations in body temperature.…”
mentioning
confidence: 99%
“…Studies involving acute exposure to ethanol support the contention that hyperbaric exposure acts as a direct antagonist to ethanol at the membrane level. As mentioned above, indirect mechanisms have been eliminated as critical factors mediating the antagonism (S, [9][10][11]. In addition, the characteristics of hyperbaric ethanol antagonism mimic those of classical pharmacological agonist-antagonist relationships in that the degree of antagonism is directly related to pressure and inversely related to the dose of ethanol (5).…”
mentioning
confidence: 99%
“…These studies at 12 ATA and lower demonstrate that pressure antagonism meets the key criteria for a direct mechanism (Syapin et al , 1988;Bejanian et al , 1993;Davies et al , 1994;Syapin et al , 1996;Davies et al , 1999;Davies and Alkana, 2001;Malcolm and Alkana, 1982;Alkana and Malcolm, 1982b;Alkana and Malcolm, 1982a;Davies et al , 2003) and selectivity (Alkana et al , 1995;Davies and Alkana, 1998;Davies et al , 1996;Davies and Alkana, 1998;Davies et al , 2001;Davies et al , 1999;Davies et al , 2003), necessary for it to be used in a manner analogous to a traditional pharmacological antagonist to help identify initial molecular sites of ethanol action and to test cause-effect relationships (Davies and Alkana, 2001). From this perspective, the sites of pressure antagonism are the same as the sites of ethanol action.…”
Section: Introductionmentioning
confidence: 95%
“…Studies show that exposure to 4–12 times normal atmospheric pressure (ATA) is a direct ethanol antagonist that blocks and reverses a broad spectrum of ethanol’s acute and chronic behavioral effects (Alkana and Malcolm, 1981;Alkana and Malcolm, 1982a;Malcolm and Alkana, 1982;Alkana et al , 1992;Nielsen et al , 1987;Bejanian et al , 1993;Davies et al , 1994;Davies et al , 1999;Davies and Alkana, 2001), as well as its effects at the biochemical (Davies and Alkana, 1998;Davies et al , 1999;Davies and Alkana, 2001) and molecular (Davies et al , 2003;Davies et al , 2004;Perkins et al , 2008) levels.…”
Section: Introductionmentioning
confidence: 99%